UPAYA MEMPERBAIKI KUALITAS GURU DENGAN MEMAKSIMALKAN TERPENUHINYA KOMPETENSI KEPRIBADIAN DAN PROFESIONALISME GURU - ismail, hafid (Jurnal Teknologi dan Bisnis, 2020)
Educator profession is a profession that is very important in the life of a nation, it is not because the position of education is very important in the context of national life. Educator is the dominant element in a process of education, so that the quality of education is determined by the quality of teachers in performing the role and duties in society. With that in mind, it is clear that the efforts to continue to develop professional educator (teacher) becomes a necessary condition for the progress of a nation, increased quality educators will lead to increased quality of education both process and outcome. Besides, the goverment should also improve system performance bad teacher to be more professional. And the effort - effort as it can increase the quality of teachers. The role of government in an effort to improve the quality of teachers is very important, the article is the government that is most responsible for the fate of the teachers. So if the government complacent or fail to take care of the fate the teacher, then this will not affect either the quality and performance of teachers. The number of personal problems that plagued the teachers, these teachers will tend to result in more focused in thinking about personal problems, so this would result in the inhibition of the smooth process of teaching and learning in schools